(untitled) (Western Pacific Surveillance and Response, 2015)
Problem: In the aftermath of Typhoon Haiyan, the World Health Organization (WHO) Representative Office in the Philippines had no social media presence to share timely, relevant public health information. Context: Risk communication is essential to emergency management for public health message dissemination. As social media sites, such as Facebook, are popular in the Philippines, these were adopted for risk communication during the response to Haiyan. Action and outcome: The WHO Representative Office in the Philippines established Facebook, Twitter and Instagram accounts. Thirty days after these social medial channels were established, a gradual increase in followers was observed. Facebook saw the largest increase in followers which occurred as posted content gradually evolved from general public health information to more pro-active public health intervention and preparedness messaging. This included information on key health interventions encouraging followers to adopt protective behaviours to mitigate public health threats that frequently occur after a disaster. Lessons learnt: During the response to Haiyan, creating a social media presence, raising a follower base and developing meaningful messages and content was possible. This event underscored the importance of building a social media strategy in non-emergency times and supported the value of developing public health messages and content that both educates and interests the general public.